2019
DOI: 10.2147/dmso.s215187
|View full text |Cite
|
Sign up to set email alerts
|

<p>Urinary biomarkers for diagnosing poststroke depression in patients with type 2 diabetes mellitus</p>

Abstract: Background Depression can seriously affect the quality of life of type 2 diabetes mellitus (T2DM) patients after stroke. However, there were still no objective methods to diagnose T2DM patients with poststroke depression (PSD). Therefore, we conducted this study to deal with this problem. Methods Gas chromatography-mass spectroscopy (GC-MS)-based metabolomics profiling method was used to profile the urinary metabolites from 83 nondepressed T2DM patients after stroke and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Therefore, to obtain more accurate potential biomarkers for PSD, researchers have done many wonderful works to successfully identify several differential urinary metabolites. 14 , 15 Meanwhile, Xie et al identified some potential metabolite biomarkers for middle-aged PSD subjects. 16 However, these identified potential biomarkers could not effectively separate elderly PSD subjects from elderly non-depressed subjects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, to obtain more accurate potential biomarkers for PSD, researchers have done many wonderful works to successfully identify several differential urinary metabolites. 14 , 15 Meanwhile, Xie et al identified some potential metabolite biomarkers for middle-aged PSD subjects. 16 However, these identified potential biomarkers could not effectively separate elderly PSD subjects from elderly non-depressed subjects.…”
Section: Discussionmentioning
confidence: 99%
“…The procedure of GC-MS analysis and samples was extracted from the previous studies. 14 , 15 The global metabolome analysis was used here. In total, 59 urinary metabolites were analyzed, and the analysis was done in Nanchang University.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Liang et al’s study ( 49 ) included 101 patients with PSD and 83 non-depressed patients after stroke. All the recruited patients were also diagnosed with type 2 diabetes mellitus (T2DM).…”
Section: Resultsmentioning
confidence: 99%
“…Another study found that several specified metabolites could act as predictors of depression recovery (46,47). Of note, recent studies (48)(49)(50)(51) showed that GC-MS-identified urinary metabolite biomarkers could significantly distinguish PSD from stroke survivors, which could be used as an objective diagnostic tool for PSD.…”
Section: Introductionmentioning
confidence: 99%